Les fonctions du langage et la déixis dans les slogans publicitaires français - Lipińska, Magdalena (Studia Romanica Posnaniensia, 2009)
The article describes speech functions and deixis in French advertising slogans. Such functions as communicative, phatic, and imperative are treated as the defining ones, whereas the last one is usually consciously hidden. The poetic and the expressive functions are considered important yet not the necessary ones, while the denotative one is often blurred. The metalinguistic function is considered secondary, however it cannot be excluded. The type of message imposes deixis' referents and syntactic functions of the latter, e.g. the subject determines the brand, producer or the service donor, a potential customer or a person who used a given product and is satisfied with it. The slogan’s deixis focuses around the major elements of the product sale.